IMPORTANCE OF IMPLEMENTING A BUSINESS PLAN IN COMPANIES - Dahiana Rotela Vazquez, Patricia; Romero Gonzalez, Yessica; Noemi Fariña Morel, Diana; David Cañete Gonzalez, Alexis; Vanessa Ruiz Diaz de Salvioni, Viviana (Revista Gênero e Interdisciplinaridade, 2023)
This article addresses the strategic importance of financial planning in the creation of sustainable companies over time, with a focus on the development of business plans. It is recognized that business plans are essential in business management and their relevance has increased due to the growing interest in entrepreneurship. The central objective of the research is to identify how financial planning influences the continuity of new companies born from business plans. The research uses a quantitative approach, with a descriptive scope. It is based on a bibliographic review of topics related to the creation of business plans and business continuity. In addition, it is complemented with experience in the evaluation of said plans. The population analyzed focuses on small and medium-sized businesses in the area of ​​km 7 and km 8 of Ciudad del Este, which responds to the objectives of the research. The survey results show that the majority of respondents understand the importance of a business plan and consider that it is essential to implement it in any type of company. Also, most would be interested in having a business plan to improve the operation of their company. In addition, many of those surveyed believe that their business would obtain better results if it had a structured business plan and that, by having such a plan, they could foresee future mishaps.